Acute Treatment with Candesartan Cilexetil, an Angiotensin II Type 1 Receptor Blocker, Improves Insulin Sensitivity in High-Fructose-Diet-fed Rats - Li, P.; Koike, T.; Jiang, H. Y.; Wang, Z. H.; Kawata, Y.; Oshida, Y. (Hormone and Metabolic Research, 2012)
We aimed to determine whether acute treatment with candesartan cilexetil (CV-11974), an angiotensin II type 1 receptor blocker (ARB) can improve insulin sensitivity in high-fructose-diet (HFD)-fed rats. In vivo glucose utilization was measured by applying the euglycemic clamp technique and the expression levels of insulin-signaling molecules in skeletal muscles were examined by western blotting. A bolus injection of CV-11974 improved the glucose infusion rate (GIR) of HFD-fed rats to the level of the control rats. Furthermore, restoration of impaired tyrosine phosphorylation of insulin receptor (IR) β, Akt phosphorylation at Ser473 and Thr308, and phosphorylation of the 160-kDa Akt substrate (AS160) in the skeletal muscles of HFD-fed rats were achieved by this treatment. These results suggest that acute administration of candesartan cilexetil can increase insulin sensitivity of HFD-fed rats, which is associated with improved insulin signaling in skeletal muscles.
Keywords: insulin sensitivity; angiotensin II type 1 receptor blocker; high-fructose diet; euglycemic clamp; insulin signaling